Detection of operating system vulnerabilities and network traffic analysis methods - Makulova, A.; Sharipova, B.; Othman, M.; Pyrkova, A.; Оrdabayeva, G. (Al-farabi Kazakh State National University, 2024)
Researchers and experts on information protection develop antivirus programs and applications to improve the security of operating systems and security policies. Threats will be relevant to organizations that do not consider security policies and regular software updates. This paper discusses applications for scanning and analysing network traffic, such as Net discover, Wireshark, and Nmap. The model network is based on a virtual machine. This research aims to determine methods for scanning and analysing network traffic and detecting network vulnerabilities. This study conducted a penetration test for Windows 10 using the Kali Purple operating system and identified the vulnerability of the operating system. The calculation of network traffic is performed with (1) the determination of the arithmetic means of network traffic, (2) the calculation of the variance, and (3) the determination of the magnitude of fluctuations relative to the average M, the range of maximum and minimum values of D, and the Hurst coefficient. As a result of the conducted research on students enrolled in the educational program 6B06301 – Information Security Systems at Farabi University, the proficiency in MS Excel and C# skills amounted to 77.11%. The research results can be used in the field of information security systems.